Different Effects of Pueraria mirifica, a Herb Containing Phytoestrogens, on LH and FSH Secretion in Gonadectomized Female and Male Rats - Suchinda Malaivijitnond; Patthama Kiatthaipipat; Wichai Cherdshewasart; Gen Watanabe; Kazuyoshi Taya (Elsevier, 2004)
To investigate the effect of Pueraria mirifica (P. mirifica) containing phytoestrogens on reproductive systems, both sexes of rats were gonadectomized and treated orally with 0, 10, 100, and 1,000 mg/kg BW per day of P. mirifica suspended in water (abbreviated as P-0, P-10, P-100, and P-1000), respectively. The treatment schedule was separated into 3 periods: pre-treatment, treatment, and post-treatment. The duration for each period was 14 days. Blood samples were taken once a week. Serum LH and FSH levels were significantly increased within 1 week after gonadectomy; and there were no changes after administration of P-0, P-10, and P-100. However, the increase of LH levels in both sexes and FSH levels in females were attenuated within 1 week after P-1,000 treatment. The attenuation of LH levels in males was smaller than that of females. The decrease of gonadotropin levels was recovered within 1 week in males and 2 weeks in females, respectively, during the post-treatment period. The increase of uterine weight and vaginal cornification were observed in female rats treated with P-100 and P-1,000, whereas only the increase of epididymis weight was found in male rats treated with P-1,000. From this study, it can be concluded that P. mirifica can influence the reproductive functions in both sexes of rats, but the response in females is greater than in males. Keywords:: Pueraria mirifica, phytoestrogen, LH, FSH, vaginal cytology